A Journal Development of Physics E-Module Based on Deep Learning Approach on Alternative Energy.: "A Case Study on Alternative Energy Topics Integrated with the Papua Context through Canva-Based Learning Media" - Siboro, Asiroha; Sebayang, Sri Rosepda Br; Simamora, Ebeneser Wacner; Yenusi, Kaleb A (COMPTON: Jurnal Ilmiah Pendidikan Fisika, 2025)
This study aims to develop and evaluate a physics e-module based on a deep learning approach, focusing on the topic of alternative energy, to enhance learning outcomes among senior high school students. Practically, the study offers an interactive learning resource aligned with deep learning principles, while theoretically, it contributes to the development of instructional media in physics education. The research used a Research and Development (R&D) design following the Four-D model: Define, Design, Develop, and Disseminate. Data collection involved questionnaires and interviews with physics teachers to identify student learning needs and contextual challenges. The module's validity was assessed by two subject matter experts and one media expert, while its practicality was evaluated by 34 students and one physics teacher using response questionnaires. The effectiveness of the e-module was determined by analyzing pretest and posttest results using N-Gain and t-test calculations. The e-module achieved a validity score of 87.75% (very valid) and a practicality score of 93.66% (very practical). It also showed significant effectiveness, with an N-Gain score of 0.714 (high category) and a t-test result of 17.84 > 2.04 (significant at α = 0.05). Therefore, the use of the deep learning approach-based physics e module is appropriate to improve student’s learning outcomes.